Heart on Fire - Bouchet, Amanda (Bouchet, Amanda. Kingmaker chronicles, 2018)
Catalia Fisa has been running from her destiny since she could crawl. Without Griffin--and apparently a few meddling gods--to push Cat along, she'd still be telling fortunes at the circus, lying about her past, ignoring her future, and living as far away from her tyrant mother as humanly possible. Cat has the power of the gods at her fingertips, and the only thing holding her back is herself.